2007
DOI: 10.1016/j.ccr.2007.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Model of Human Ovarian Endometrioid Adenocarcinoma Based on Somatic Defects in the Wnt/β-Catenin and PI3K/Pten Signaling Pathways

Abstract: One histologic subtype of ovarian carcinoma, ovarian endometrioid adenocarcinoma (OEA), frequently harbors mutations that constitutively activate Wnt/beta-catenin-dependent signaling. We now show that defects in the PI3K/Pten and Wnt/beta-catenin signaling pathways often occur together in a subset of human OEAs, suggesting their cooperation during OEA pathogenesis. Deregulation of these two pathways in the murine ovarian surface epithelium by conditional inactivation of the Pten and Apc tumor suppressor genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
305
4
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(331 citation statements)
references
References 51 publications
19
305
4
3
Order By: Relevance
“…In this case, the mutant Kras is able to contribute to tumorigensis not only via PI3K activation but via a number of other signaling pathways. In addition, Wu et al showed that a combination of Pten loss and Apc loss, but not the single lesions, resulted in aggressive tumors (45).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the mutant Kras is able to contribute to tumorigensis not only via PI3K activation but via a number of other signaling pathways. In addition, Wu et al showed that a combination of Pten loss and Apc loss, but not the single lesions, resulted in aggressive tumors (45).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PTEN might also affect b-catenin signaling through the suppression of PI3K/Akt signaling, suggesting a reciprocal relationship between the PTEN/PI3K/Akt and b-catenin signaling pathways (Persad et al, 2001). In addition, these two pathways have been shown to cooperate in tumor formation, as conditional inactivation of Pten and Apc in murine ovarian surface epithelium results in the formation of tumors that resemble human endometrioid ovarian carcinomas (Wu et al, 2007).…”
Section: Regulation Of Pten Levels By Cell Density and E-cadherin-cadmentioning
confidence: 99%
“…Ovarian surface epithelium was infected with replication-deficient recombinant adenovirus expressing Cre recombinase (15), a kind gift from Walter Thomas' Laboratory, Baker Institute, Australia, by methods previously described (13,16,17). Briefly, ovulation was synchronized by i.p.…”
Section: Adenoviral-cre Recombination In Ovarymentioning
confidence: 99%